Faith-Based Correctional Rehabilitation: Cultivating Moral Resilience and Character Transformation in Inmates - Rahmi Hidayanti; Mila Siti Azizah (Faculty Ushuluddin, Adab and Dakwah UIN Palangka Raya, 2025)
Conventional carceral rehabilitation frameworks often prioritize institutional discipline and vocational skills while marginalizing the spiritual dimension, despite inmates frequently experiencing existential crises, loss of self-concept, and severe carceral stress. This study aims to analyze the implementation of the structured spiritual guidance program at the Class IIB Kebumen State Detention Center, its challenges, and its impact on inmate character building. Adopting a descriptive qualitative approach, data were gathered via participant observation, documentary reviews, and semi-structured in-depth interviews with five purposively selected key informants, including institutional authorities, external religious mentors, and active inmates. Data trustworthiness was established through technical and source triangulation, and analyzed using the Miles and Huberman interactive model. The findings demonstrate that the detention center has systematically integrated a structured spiritual curriculum—including communal sermons, collective dhikr, and Quranic literacy—by forging strategic partnerships with external religious and academic bodies. Operationalized through planning, execution, and monitoring phases, the program utilizes an adaptive, tripartite approach (individual, group, and collaborative) that accommodates diverse inmate backgrounds. Active participation in the program successfully catalyzes positive behavioral modification, enhances emotional regulation, and reconstructs a resilient, prosocial self-concept, thereby elevating inmates' psychological readiness for social reintegration. However, long-term efficacy is hindered by systemic bottlenecks, including fragmented scheduling, varying baseline religious literacy, and a lack of integrated curricular alignment with vocational tracks. This study concludes that a collaborative, multi-dimensional ecosystem combining institutional support, staff engagement, and inmate motivation is paramount to sustaining faith-based correctional rehabilitation.